Microbial Content Generation for Natural Terrains in Computer Games - Lamers, Maarten H.; van Eck, Wim J. O. M. (Frontiers in Computer Science, 2022)
Procedural content generation (PCG) has been applied since several decades to fulfil various game-related design needs. Besides bio-inspired methods, living (non-human) organisms were used in computer games for various purposes, such as behaviour generation, data gathering, and player education. No living organisms were used for the generation of virtual terrains in games. Such an approach to terrain generation could benefit from morphological similarity between natural terrains and colonies of microbial organisms, real-time development of terrains over time, and educational opportunities. We successfully executed an experiment in which we used growing bacterial and fungal cultures for generating naturally appearing virtual terrains in real-time. Concludingly, we confirm the feasibility of using living organisms in real-time non-behavioural PCG and reflect on its potential impact.